2018
DOI: 10.2340/16501977-2334
|View full text |Cite
|
Sign up to set email alerts
|

Effect of balance training on falls in patients with osteoporosis: A systematic review and meta-analysis

Abstract: Balance training may significantly reduce the frequency of falls in patients with osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…knowledge of osteoporosis, medications, diet and exercise) and advice for daily weight-bearing physical activity are appropriate [43][44][45]. Where indicated, the addition of fall prevention measures, including supervised exercise and/or rehabilitation, has been shown to be useful in reducing falls [46,47] but the effects on fracture risk remain uncertain [47].…”
Section: Impact On Treatmentmentioning
confidence: 99%
“…knowledge of osteoporosis, medications, diet and exercise) and advice for daily weight-bearing physical activity are appropriate [43][44][45]. Where indicated, the addition of fall prevention measures, including supervised exercise and/or rehabilitation, has been shown to be useful in reducing falls [46,47] but the effects on fracture risk remain uncertain [47].…”
Section: Impact On Treatmentmentioning
confidence: 99%
“…The most consistent predictor of future falls is a diagnosis of gait or balance abnormalities [9]. Therefore, balance training exercises play a key role in reducing the frequency of falls and preventing further fall-related injuries [10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the fall frequency in the training group was lower than that of the nontraining group (−0.77 ± 1.76 vs. 0.03 ± 0.98, P =0.018). Another recent meta-analysis [ 31 ] also confirmed that balance training was significantly associated with a decreased frequency of falls in osteoporosis patients.…”
Section: Discussionmentioning
confidence: 84%